Sejarah Pemekaran Kabupaten Malinau (1999-2006) - Datuk Divan Iqbal Viranda; Muhammad Azmi; Muhamad Sopyan (Langgong: Jurnal Ilmu Sosial dan Humaniora, 2021)
Malinau Regency was originally one of the sub-districts in Bulungan Regency, on October 12, 1999 there was a regional division where Malinau was separated from Bulungan Regency to become its own regency. The purpose of this study was to find out the background of the division and how the development of Malinau District after the division occurred from 1999 to 2006. This type of research is a historical research with a four-stage historical method which includes heuristics, criticism, interpretation, and historiography. The results showed that the background of the division of Malinau into a district was a decision taken by the Regional Government of Bulungan Regency which at that time was led by Regent R.A. Besing. On the grounds that the area of ​​Bulungan Regency at that time, if not divided, would experience a gap because it had a very large area at that time, it was necessary for him to split this area into 3 regencies, namely Bulungan Regency itself, Malinau Regency, and Nunukan Regency. After the division took place, it certainly had an impact on the people of Malinau, both in terms of economy, education, and health. From the economic aspect itself, it has increased from 2006 to Rp. 554.07 billion. Then in the same year, the education sector also experienced an increase which reached 113 school buildings, as well as for the health aspect it had reached 121 units of health facilities including hospitals, posyandu, and posyandu assistants in 2006